Early retirement provision for elderly displaced workers - Herman Kruse; Andreas Myhre (Statistics Norway, Research Department, 2022)
This paper studies the economic effects on re-employment and program substitution behavior among elderly displaced workers who exogenously lose eligibility for their early retirement option. We use detailed Norwegian matched employer-employee data containing information on bankruptcy dates and individual-level wealth, income, pensions and social security benefits. Our empirical strategy employs a regression discontinuity design, as job displacement before a certain age cut-off results in the loss of eligibility for early retirement benefits between ages 62-67 years in Norway. We find that re-employment rates are indistinguishable between workers who just retain eligibility for early retirement benefits and those who just do not. Meanwhile, those who lose eligibility offset 69% of their lost benefits through take-up of other social security benefits, where 51 percentage points comes from disability insurance and 13 percentage points from unemployment insurance. Our findings are particularly policy relevant as tightening of age-limits for old-age pensions is on the agenda in several OECD countries, while current economic hardship throughout the region may lead to increased job displacement for elderly workers.
Keywords: H55; I38; J14; J26; J65; 330; early retirement; job displacement; labor supply; benefit substitution; social security